2011
DOI: 10.1007/s11605-011-1486-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Perforated Appendicitis: Effect of Delay Is Confounded by Age and Gender

Abstract: There is an early risk of perforated appendicitis even within the first 36 h of symptoms. This risk appears to be higher in males and patients older than 55 years, a quarter of whom are perforated within the first 36 h of symptom duration. Additionally, perforation in acute appendicitis may be more of a continuous phenomena worsening exponentially with duration of symptoms rather than a threshold phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 27 publications
(36 reference statements)
7
75
1
Order By: Relevance
“…As found by others [1,5,11,12], girls had a significantly higher frequency of negative appendectomies. Of note, despite no difference in time to appendectomy, boys had a higher perforation frequency, which has been reported in adult men before [13,14], but not in boys [12]. It could be speculated to be related to different immune responses or differences in the intestinal connective tissue between the genders.…”
Section: Discussionmentioning
confidence: 77%
“…As found by others [1,5,11,12], girls had a significantly higher frequency of negative appendectomies. Of note, despite no difference in time to appendectomy, boys had a higher perforation frequency, which has been reported in adult men before [13,14], but not in boys [12]. It could be speculated to be related to different immune responses or differences in the intestinal connective tissue between the genders.…”
Section: Discussionmentioning
confidence: 77%
“…[14][15][16] Barreto et al [8] have found that male sex and being older than 60 are significantly associated with a risk of perforation. Augustin et al [17] have obtained the same results in patients older than 50. Similarly, Sulu et al [18] have found that the perforation rate is higher in elderly patients.…”
Section: Discussionmentioning
confidence: 56%
“…17 About 50% of the children with complicated appendicitis had a leucocyte count of more than 15,000 cells/mm.…”
Section: Discussionmentioning
confidence: 99%